Additive of lithium ion battery electrolyte, electrolyte and lithium ion secondary battery

By using compound additives with specific structures in the lithium-ion battery electrolyte, an electrolyte formed at the same time on the positive and negative electrodes is solved, the performance deterioration of lithium-ion batteries in the use of high-nickel positive electrode materials and graphite or silicon negative electrode materials is solved. Significantly improves the battery's circulation, magnification and high temperature performance.

CN119495816APending Publication Date: 2025-02-21MURATA MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311035154.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In the use of high-nickel positive electrode materials and graphite or silicon negative electrode materials, existing lithium-ion batteries have problems such as oxidation decomposition, gas production, side reactions and instability of solid electrolyte interface (SEI) films, resulting in deterioration of battery performance and shortening of service life. .

Method used

Provided is a lithium-ion battery electrolyte additive containing a compound having a specific structure, which can form a film on the positive and negative electrodes simultaneously, and form a stable and dense conductive polymerization by combining thiophene functional groups and vinyl sulfite or vinyl sulfate functional groups. The film inhibits oxidative decomposition and dissolution of transition metals.

Benefits of technology

This technical method can significantly improve the circulation performance, rate performance, high-temperature storage performance and low-temperature discharge performance of lithium-ion batteries, extend the service life of the battery, and maintain the stability of battery performance at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495816A_ABST
    Figure CN119495816A_ABST
Patent Text Reader

Abstract

The invention provides an additive for a lithium ion battery electrolyte, an electrolyte containing the additive and a lithium ion secondary battery. Specifically, the invention provides an additive for a lithium ion battery electrolyte, the additive comprises a compound with a structure shown as a formula (1) and / or a formula (2), R1 and R2 are respectively and independently substituted or unsubstituted # imgabs0 #, and n is an integer greater than 0; the invention further discloses an electrolyte containing the additive and used for the lithium ion battery and the lithium ion battery containing the electrolyte. # imgabs1 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion secondary batteries, and in particular to an additive for lithium ion battery electrolyte, an electrolyte containing the additive, and a lithium ion secondary battery. Background Art

[0002] In recent years, with the continuous development of electronic technology, people's demand for battery devices used to support the energy supply of electronic devices has been increasing. Nowadays, batteries that can store more electricity and output high power are needed. Traditional lead-acid batteries and nickel-metal hydride batteries can no longer meet the needs of new electronic products. Therefore, lithium batteries have attracted widespread attention. In the process of developing lithium batteries, their capacity and performance have been effectively improved. Lithium-ion batteries are widely used in 3C digital products, power tools, electric vehicles, aerospace and other fields due to their advantages such as high operating voltage, high energy density, long life, wide operating temperature range and environmental friendliness.

[0003] In order to improve the energy density of lithium-ion batteries, a common measure is to select a high-nickel positive electrode material / silicon-doped negative electrode material system. However, with the increase of the nickel content of the positive electrode, the oxidizability of the high-nickel positive electrode material in the de-lithiated state is significantly enhanced, and the electrolyte is very easy to oxidize and decompose on the surface of the high-nickel positive electrode material in the de-lithiated state, aggravating the gas production problem of lithium-ion batteries and deteriorating the cycle performance of lithium-ion batteries. In addition, the high-voltage positive electrode active material itself is also very unstable when it is lithium-deficient, and it is easy to have some side reactions, such as releasing oxygen and dissolving transition metal ions, which cause the transition metal ions to separate from the crystal and enter the electrolyte as the reaction proceeds, catalyzing the decomposition of the electrolyte and damaging the passivation film of the active material. At the same time, the transition metal lithium ions will also occupy the lithium ion migration channel of the passivation film on the surface of the negative electrode material, hindering the migration of lithium ions, thereby affecting the service life of the battery. In addition, in terms of the negative electrode, the solid electrolyte interface (SEI) film on the surface of the graphite or silicon negative electrode is unstable due to the huge volume change during the charge and discharge process, which seriously affects the performance of the battery.

[0004] At present, the main method to solve the above problems is to add positive and negative electrode film-forming additives respectively, and improve the high and low temperature, cycle and rate performance of the battery through the combination of additives. Among them, as negative electrode film-forming additives, vinyl sulfate (DTD) and vinyl sulfite have been successfully applied in ternary material batteries in recent years, which can mainly increase the initial discharge capacity, effectively reduce the impedance of the negative electrode, and have a good improvement effect on the high and low temperature performance and cycle performance of the battery. However, vinyl sulfate and vinyl sulfite additives can only form a film at low temperature or room temperature to improve the cycle and impedance performance of the battery, and the additive is unstable at high temperature (such as 60°C), so it will deteriorate the battery performance at high temperature. As a positive electrode film-forming additive, cyclic sultone compounds can be oxidized and decomposed on the surface of the positive electrode to form a passivation film, effectively reducing the oxidative decomposition of the electrolyte at the positive electrode, further reducing the gas production of the battery, and extending the storage life of the battery. However, cyclic sultone compounds will continuously oxidize and form polymers on the surface of the positive electrode during the battery cycle and storage process, causing the positive electrode interface impedance to continue to increase, affecting the power performance of the battery. In addition, thiophene compounds, as electrolyte additives, can form a stable and dense interfacial film on the positive electrode surface at high voltage, inhibiting the oxidative decomposition of the solvent, thereby improving the safety performance of lithium-ion batteries and the cycle performance at high voltage (>4.5V).

[0005] The use of the additive combination of the prior art not only requires the addition of positive and negative electrode film-forming additives separately, resulting in more complicated steps and higher use costs, but also may cause the problem of battery performance deterioration caused by the additives as described above. Therefore, there is a need in the art for a lithium-ion battery electrolyte additive that can form a film on both the positive and negative electrodes and significantly improve battery performance. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an electrolyte additive for lithium ion batteries that can form films on positive and negative electrodes at the same time and significantly improve battery performance, as well as an electrolyte and a lithium ion secondary battery containing the same.

[0007] In order to achieve the above object, according to one aspect of the present invention, the present invention provides an additive for lithium ion battery electrolyte, the additive comprising a compound having a structure of formula (1) and / or formula (2):

[0008]

[0009] Where R 1 and R 2 are independently substituted or unsubstituted Wherein n is an integer greater than 0.

[0010] Furthermore, in the above-mentioned additives, in formula (1) and formula (2), n=1 or 2.

[0011] Furthermore, in the above-mentioned additives, the compound having the structure of formula (1) is:

[0012]

[0013] The compound having the structure of formula (2) is:

[0014]

[0015] According to another aspect of the present invention, an electrolyte for a lithium ion battery is provided, the electrolyte comprising the additive according to any one of the aforementioned aspects of the present invention, an organic solvent and a lithium salt.

[0016] Furthermore, in the above electrolyte, based on 100 parts by weight of the organic solvent and the lithium salt, the amount of the additive is greater than 0.01 parts by weight and less than or equal to 0.50 parts by weight, preferably 0.10 parts by weight to 0.50 parts by weight.

[0017] Furthermore, in the above electrolyte, the organic solvent includes cyclic carbonate, linear carbonate, or any combination thereof.

[0018] Furthermore, in the above electrolyte, the lithium salt is selected from LiCl, LiBr, LiPF 6 , LiBF 4 、LiAsF 6 、LiClO 4 、LiB(C 6 H 5 ) 4 、LiCH 3 SO 3 、LiCF 3 SO 3 、LiN(SO 2 CF 3 ) 2 、LiC(SO 2 CF 3 ) 3 、LiAlCl 4 , Li 2 SiF 6 , or a combination thereof.

[0019] According to another aspect of the present invention, a lithium-ion secondary battery is provided, comprising: a positive electrode sheet, a negative electrode sheet, a separator, and the electrolyte according to any one of the aforementioned aspects of the present invention.

[0020] Furthermore, in the above lithium-ion secondary battery, the positive electrode sheet comprises a high-nickel positive electrode material.

[0021] Furthermore, in the above lithium-ion secondary battery, the negative electrode sheet comprises graphite or silicon negative electrode material.

[0022] The additive for lithium ion battery electrolyte, the electrolyte containing the additive and the lithium ion secondary battery of the present invention can form a film on the positive and negative electrodes at the same time and significantly improve the battery performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0024] Figure 1 is a graph showing the cycle impedance of batteries manufactured according to Examples 1 and 2 of the present invention and Comparative Example 1.

[0025] Figure 2 is a graph showing the cycle retention rates of batteries manufactured according to Examples 1 and 2 of the present invention and Comparative Example 1.

[0026] Figure 3 is a graph showing HOMO and LUMO values ​​of vinyl sulfate (DTD), thiophene, and exemplary compounds of the present invention. DETAILED DESCRIPTION

[0027] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0028] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present application.

[0029] As described in the background technology section, in order to improve the performance of lithium batteries, for example, to solve the gas production and instability problems of high-nickel positive electrode materials, and the volume change problem of graphite or silicon negative electrode materials, the electrolyte system used for lithium-ion batteries in the prior art often requires the addition of positive and negative electrode film-forming additives respectively, and the vinyl sulfate and vinyl sulfite additives in the prior art are unstable at high temperatures, and cyclic sulfone additives can lead to problems such as increased impedance and deterioration of power performance.

[0030] In view of the above problems, the present invention provides an additive for lithium-ion battery electrolyte, an electrolyte and a lithium-ion secondary battery containing the additive, which solves the above problems in the prior art and provides an electrolyte system for lithium-ion batteries that can form films on positive and negative electrodes at the same time and significantly improve battery performance.

[0031] According to a typical embodiment of the present application, an additive for lithium-ion battery electrolyte is provided, the additive comprising a compound having a structure of formula (1) and / or formula (2):

[0032]

[0033] Where R 1 and R 2 are independently substituted or unsubstituted Wherein n is an integer greater than 0.

[0034] The inventors unexpectedly found that by combining the thiophene functional group with the vinyl sulfite or vinyl sulfate functional group, the advantages of both can be utilized at the same time, wherein the thiophene group can form a dense and uniform conductive polymer film at the cathode oxidation, stabilize the oxidative decomposition of the electrolyte and the cathode interface under extreme environmental conditions, inhibit the dissolution of transition metals, effectively isolate the contact between the positive electrode material and the electrolyte in the high oxidation state during the charging and discharging process of the secondary battery, avoid the chemical corrosion of the generated HF on the negative electrode silicon-based material, and ensure the excellent high temperature and high pressure performance of the battery. At the same time, the cyclic vinyl sulfite and vinyl sulfate functional groups can form films at the positive and negative electrodes to reduce the impedance of the battery. The compounds of formula (1) and (2) of the present invention combine the cyclic vinyl sulfite and vinyl sulfate functional groups with the thiophene functional group, on the one hand, avoid adding a variety of additives, and on the other hand, effectively improve the cycle performance, rate performance, high temperature storage performance and low temperature discharge performance of the lithium ion battery, while overcoming the unstable characteristics of vinyl sulfite or vinyl sulfate at high temperatures, and improving the high temperature performance of the battery.

[0035] In order to combine the advantages of electrolyte additive materials in the prior art and overcome the shortcomings of adding multiple additives, the inventors refer to the frontier orbital theory for the development of the new electrolyte additive of the present invention. The frontier orbital theory believes that: during the reaction of substances, it is the molecular orbitals that interact with each other, among which the frontier orbitals take precedence, and the frontier orbitals reflect the physical and chemical properties of the substance to a large extent. The higher the energy of the highest occupied molecular orbital (HOMO) of the molecule, the easier it is to lose electrons and be oxidized; on the contrary, the lower the energy of the lowest unoccupied molecular orbital (LUMO), the easier it is to gain electrons and be reduced. Using functional density theory (DFT), the HOMO and LUMO values ​​of a certain molecular structure are simulated and calculated, which can be used to infer the oxidation resistance and reduction resistance of the substance. Figure 3The HOMO and LUMO values ​​of DTD, thiophene and several exemplary compounds envisioned by the present invention: terthiophene DTD (TriTh–DTD), bisthiophene DTD (BiTh-DTD), and thiophene DTD (Th-DTD) calculated using the frontier orbital theory. Among them, the HOMO values ​​are: TriTh–DTD>BiTh-DTD>thiophene>Th-DTD>DTD. It can be predicted from the HOMO value that the compound envisioned by the present invention is more easily oxidized than DTD, which is beneficial to the film formation at the positive electrode. It can be predicted from the LUMO value that the compound envisioned by the present invention is more easily reduced than thiophene. Therefore, it can be inferred that the compound envisioned by the present invention combines the advantages of DTD and thiophene, can form films at the positive and negative electrodes at the same time, and improve the overall performance of the battery. In addition, the inventors also found that when vinyl sulfate (DTD) is replaced by vinyl sulfite, similar results will be obtained.

[0036] In some embodiments of the present invention, in formula (1) and formula (2), n = 1 or 2. The inventors have found that in the above formula (1) and formula (2), the best performance compound can be obtained when n = 1 or 2. When the value of n is too large, it may lead to degradation of battery performance.

[0037] In some embodiments of the present invention, the compound having the structure of formula (1) is:

[0038]

[0039] The compound having the structure of formula (2) is:

[0040]

[0041] The inventors have found that the above-mentioned thienyl vinyl sulfite and thienyl vinyl sulfate compounds provide the best balance in terms of performance, cost and ease of manufacturing. They can achieve the above-mentioned positive and negative electrode simultaneous film formation and significantly improve the battery performance while having relatively low manufacturing cost and ease. Nevertheless, the thienyl vinyl sulfate compound still belongs to the scope of the present invention.

[0042] According to another typical embodiment of the present invention, an electrolyte for a lithium-ion battery is provided, the electrolyte comprising the additive according to any one of the aforementioned aspects of the present invention, an organic solvent and a lithium salt.

[0043] In a preferred embodiment, in the above electrolyte, based on 100 parts by weight of the organic solvent and the lithium salt, the amount of the additive is greater than 0.01 parts by weight and less than or equal to 0.50 parts by weight, preferably 0.10 parts by weight to 0.50 parts by weight.

[0044] The inventors have found that the additive of the present invention is most beneficial to battery performance when present in the electrolyte at the above content. When the amount of the additive is too small, the effect is not obvious; when the amount of the additive is greater than 0.50 parts by weight, it will be difficult to dissolve in the electrolyte.

[0045] In a preferred embodiment, in the above electrolyte, the organic solvent includes cyclic carbonate, linear carbonate, or any combination thereof.

[0046] In a preferred embodiment, in the above electrolyte, the lithium salt is selected from LiCl, LiBr, LiPF 6 , LiBF 4 、LiAsF 6 、LiClO 4 、LiB(C 6 H 5 ) 4 、LiCH 3 SO 3 、LiCF 3 SO 3 、LiN(SO 2 CF 3 ) 2 、LiC(SO 2 CF 3 ) 3 、LiAlCl 4 , Li 2 SiF 6 , or a combination thereof.

[0047] According to another typical embodiment of the present invention, a lithium-ion secondary battery is provided, comprising: a positive electrode sheet, a negative electrode sheet, a separator, and the electrolyte according to any one of the aforementioned aspects of the present invention.

[0048] Furthermore, in the above lithium-ion secondary battery, the positive electrode sheet comprises a high-nickel positive electrode material.

[0049] Furthermore, in the above lithium-ion secondary battery, the negative electrode sheet comprises graphite or silicon negative electrode material.

[0050] As described above, the inventors have found that the additives according to the present invention can form films on the positive and negative electrodes at the same time, thereby being able to simultaneously improve the gas production problem caused by the easy oxidation and decomposition of the surface of the high-nickel positive electrode material, the side reaction problem caused by the instability of the high-nickel positive electrode material, and the volume change problem during the charge and discharge process of the graphite or silicon negative electrode, thereby significantly improving the battery performance.

[0051] In summary, compared with the prior art, the present invention can inhibit gas production, effectively improve the cycle performance of the battery under high temperature and high pressure, reduce the battery impedance, and improve the discharge capacity and rate performance of the battery by adding the additive according to the present invention to a conventional electrolyte (such as a cyclic carbonate solvent, a linear carbonate solvent and a lithium salt).

[0052] The present invention will be described in detail below through examples. Each example only lists key technical indicators, but the present invention is not limited to these examples.

[0053] Comparative Example 1

[0054] The lithium ion battery used in Comparative Example 1 was prepared by the following steps.

[0055] Preparation of positive electrode sheet: The positive electrode active material is lithium nickel cobalt aluminum oxide NCA (specifically LiNi 0.8 Co 0.15 Al 0.05 O 2 ) (95.50 g), conductive carbon black (2.50 g), binder polyvinylidene fluoride (1.90 g) and dispersant polyvinyl pyrrolidone (0.10 g) were mixed to obtain a positive electrode mixture, and the positive electrode mixture was dispersed in N-methylpyrrolidone to obtain a positive electrode mixture slurry. The positive electrode mixture slurry was then applied to a positive electrode collector made of aluminum foil, which was dried and stamped to form a positive electrode sheet.

[0056] Preparation of negative electrode sheet: A mixture of negative electrode active material silicon oxide and graphite powder (wherein the weight ratio of silicon oxide to graphite is 9:1) (95.85g), conductive carbon black (1.00g), binder carboxymethyl cellulose and styrene butadiene latex (3.15g) and an appropriate amount of water were stirred to prepare a negative electrode mixture slurry. The negative electrode mixture slurry was then uniformly coated on a negative electrode collector made of copper foil, dried and stamped to form a negative electrode sheet.

[0057] Preparation of electrolyte: Ethylene carbonate (20.00 g), dimethyl carbonate (62.00 g) and lithium hexafluorophosphate (18.00 g) were mixed to prepare a basic electrolyte.

[0058] Battery assembly: CR2016 button cells were assembled in a dry laboratory. The positive electrode sheet, negative electrode sheet, electrolyte, separator and button cell shell prepared in the above steps were assembled. After the battery was assembled, it was left to stand for 12 hours to age and obtain an NCA button cell.

[0059] Comparative Example 2

[0060] A lithium ion battery was prepared using the same steps as in Comparative Example 1. The difference was that in the electrolyte preparation step, 0.50 g of a commercially available vinyl sulfite additive (CAS No.: 3741-38-6, Sigma-Aldrich) was added to 100.00 g of the prepared basic electrolyte.

[0061] Example 1

[0062] The lithium ion battery of Example 1 was prepared using the same steps as those of Comparative Example 1. The difference was that, in the step of preparing the electrolyte, 0.50 g of additive A1 (i.e., the compound of formula (3) of the present invention) was added to 100.00 g of the prepared basic electrolyte.

[0063] Example 2

[0064] The lithium ion battery of Example 2 was prepared using the same steps as those of Comparative Example 1. The difference was that, in the step of preparing the electrolyte, 0.50 g of additive A2 (i.e., the compound of formula (4) of the present invention) was added to 100.00 g of the prepared basic electrolyte.

[0065] Example 3

[0066] The lithium ion battery of Example 3 was prepared using the same steps as those of Comparative Example 1. The difference was that, in the step of preparing the electrolyte, 0.10 g of additive A1 (i.e., the compound of formula (3) of the present invention) was added to 100.00 g of the prepared basic electrolyte.

[0067] Example 4

[0068] The lithium ion battery of Example 4 was prepared using the same steps as those of Comparative Example 1. The difference was that, in the step of preparing the electrolyte, 0.10 g of additive A2 (i.e., the compound of formula (4) of the present invention) was added to 100.00 g of the prepared basic electrolyte.

[0069] Example 5

[0070] The lithium ion battery of Example 5 was prepared using the same steps as those of Comparative Example 1. The difference was that, in the step of preparing the electrolyte, 0.01 g of additive A1 (i.e., the compound of formula (3) of the present invention) was added to 100.00 g of the prepared basic electrolyte.

[0071] The batteries in the above embodiments and comparative examples were first subjected to a 0.1C cycle test at 25°C for one time, and then the initial impedance was tested. Then, a 1C charge and 5C discharge cycle test was performed at 60°C for 100 times to determine the capacity retention rate of the battery after 100 cycles, and then the post-cycle impedance was tested. The test results are shown in Table 1 below.

[0072] Table 1

[0073]

[0074]

[0075] In the above Table 1, by comparing the results of Examples 1 and 3 (using the additive A1 of the present invention (3)) and Examples 2 and 4 (using the additive A2 of the present invention (4)) with the results of Comparative Example 1, it can be seen that the lithium ion battery made with the electrolyte containing the additive of the present invention shows improvement in both cycle retention and post-cycle impedance compared with the lithium ion battery made with the electrolyte not containing the additive of the present invention. Figure 1 and Figure 2 It can also be seen that the batteries manufactured according to Examples 1 and 2 show improvements in cycle retention and post-cycle impedance compared to the battery of the comparative example.

[0076] In addition, by comparing the results of Examples 1 and 3 (using the additive A1 of the formula (3) of the present invention) and Examples 2 and 4 (using the additive A2 of the formula (4) of the present invention) with the results of Comparative Example 2, it can be seen that compared with the lithium ion battery made using the vinyl sulfite additive of the prior art, the lithium ion battery made using the electrolyte containing the additive of the present invention shows improvement in both the cycle retention rate and the post-cycle impedance.

[0077] In addition, by comparing Examples 1-5, it can be seen that when the amount of the additive of the present invention in the electrolyte is greater than 0.01 parts by weight and less than or equal to 0.50 parts by weight, the lithium ion battery made using the electrolyte containing the additive of the present invention shows improvement in cycle retention and post-cycle impedance. In particular, when the amount of the additive of the present invention in the electrolyte is 0.10 parts by weight to 0.50 parts by weight, the lithium ion battery made using the electrolyte containing the additive of the present invention shows improvement in cycle retention and post-cycle impedance.

[0078] In summary, by using the additive of the present invention in the electrolyte of a lithium-ion battery, especially adding the additive of the present invention in the specific amount specified in the present invention, the cycle retention rate and post-cycle impedance of the lithium-ion battery can be effectively improved. Compared with the electrolyte additives of the prior art, there are improvements in battery performance, use cost, etc.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An additive for lithium ion battery electrolyte, characterized in that: The additive comprises a compound having a structure of formula (1) and / or formula (2): Where R 1 and R 2 are independently substituted or unsubstituted Wherein n is an integer greater than 0.

2. The additive according to claim 1, characterized in that In formula (1) and formula (2), n=1 or 2.

3. The additive according to claim 1 or 2, characterized in that The compound having the structure of formula (1) is: The compound having the structure of formula (2) is:

4. An electrolyte for a lithium ion battery, characterized in that: The electrolyte comprises the additive according to any one of claims 1 to 3, an organic solvent and a lithium salt.

5. The electrolyte according to claim 4, characterized in that Based on 100 parts by weight of the organic solvent and the lithium salt, the amount of the additive is greater than 0.01 parts by weight and less than or equal to 0.50 parts by weight, preferably 0.10 parts by weight to 0.50 parts by weight.

6. The electrolyte according to claim 4, characterized in that The organic solvent includes cyclic carbonate, linear carbonate, or any combination thereof.

7. The electrolyte according to claim 4, characterized in that The lithium salt is selected from the group consisting of LiCl, LiBr, LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiAlCl4, Li2SiF6, or a combination thereof.

8. A lithium ion secondary battery, characterized in that: include: Positive electrode, Negative electrode, Diaphragm, and The electrolyte according to any one of claims 4 to 7.

9. The lithium ion secondary battery according to claim 8, characterized in that: The positive electrode sheet comprises a high-nickel positive electrode material.

10. The lithium ion secondary battery according to claim 8 or 9, characterized in that: The negative electrode sheet comprises graphite or silicon negative electrode material.